Sustainable Value: Corporate Responsibility and measuring the Financial and Non- financial performance of the firm - Grayson, David (Cranfield University, 2009)
This is the final report from a two-year EABIS funded research project. The purpose of the research has been to explore how the environmental, social and governance performance of companies might impact on the drivers of business success; how companies explain these linkages to investors, and how the investment community treats these data. The research project has been run in close contact with a parallel EU CSR Alliance Laboratory on “Corporate Responsibility and the market-valuation of non-financial performance”. This Lab has been led by Lloyds Banking Group and Telecom Ita